FAKTOR-FAKTOR YANG MEMPENGARUHI BURNOUT PADA TENAGA KESEHATAN INSTALASI PELAYANAN RADIOLOGI DAN KEDOKTERAN NUKLIR RSUPN CIPTO MANGUNKUSUMO TAHUN 2021 - Astuti, Dita Ayu; Hernaya, Ade; Nabila, Anggun; Kusumaningtiar, Devi Angeliana (Jurnal Kesehatan Masyarakat (Undip), 2022)
Health workers are workers who play an important role in hospitals, with daily work dealing with patients. Burnout syndrome is often found in professions that are human service, such as health workers. Burnout is exhaustion both physically, emotionally and mentally as a result of long-term involvement in situations with emotional demands. The purpose of this study was to determine the factors that influence burnout of health workers at the Radiology and Nuclear Medicine Service Installation at Cipto Mangunkusumo General Hospital. The type of research used is cross sectional with a quantitative approach. The study was conducted in July – September 2021. The population and sample were 66 health workers with total sampling method. Data analysis was carried out using univariate and bivariate tests using the chi-square statistical test with = 0.05. The conclusion from the results of this study is that health workers experienced high burnout by 36 pople  (57,1 %), 27 people low burnout (42,9 %), health workers with a working period of 5 years 53 people (84.1%), years of service <5 years 10 people (15.9 %), very high workload 33 people (52.4 %), high workload 23 people (36.5 %), low workload 7 people (11.1% %), low social support 40 people (63.5 %), and high social support 23 people (36.5 %). Based on bivariate analysis, it was found that there was a relationship between burnout and workload (p-value = 0.028, with PR = 2.563). The risk factors for burnout of health workers in this study were years of work, workload, and social support